2022
DOI: 10.1136/bmjsrh-2022-201480
|View full text |Cite
|
Sign up to set email alerts
|

Views of clinicians towards providing contraceptive advice and contraception to women following early pregnancy loss: a qualitative study

Abstract: IntroductionNational guidelines advise that clinicians caring for women post-pregnancy should give women opportunities to discuss contraception, regardless of pregnancy outcome, and provide contraception to women who choose to take up a method. This study aimed to explore knowledge, views and needs of Early Pregnancy Unit (EPU) clinicians around discussing and offering contraception and discussing pregnancy intendedness with women after early pregnancy loss using a qualitative approach.MethodsSemi-structured, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A study of the potential introduction of the LMUP into early pregnancy units described clinician’s thoughts on asking about pregnancy intendedness as ‘polarized’, with some considering it essential and others insensitive 30 . Importantly, this study was hypothetical and, prior to being asked, none of the nurses interviewed knew of the LMUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the potential introduction of the LMUP into early pregnancy units described clinician’s thoughts on asking about pregnancy intendedness as ‘polarized’, with some considering it essential and others insensitive 30 . Importantly, this study was hypothetical and, prior to being asked, none of the nurses interviewed knew of the LMUP.…”
Section: Discussionmentioning
confidence: 99%
“…JH developed a framework with high-level themes at the individual level of midwife and woman, organizational level and external factors, based on other research 29 , 30 , and sub-themes based on the data, and discussed with BS and CS. The transcripts were indexed by CS, BS and JH.…”
Section: Methodsmentioning
confidence: 99%
“…Before using our EMR intervention, providers rarely discussed contraception with patients who had a resolved pregnancy of unknown location. In a qualitative study, investigators sought to explore clinicians’ views surrounding discussing contraception with patients after early pregnancy loss [ 6 ]. Within this study, they found that clinicians were reluctant to discuss contraception, and they also highlighted a barrier to providing contraceptive counseling as a lack of time [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, investigators sought to explore clinicians’ views surrounding discussing contraception with patients after early pregnancy loss [ 6 ]. Within this study, they found that clinicians were reluctant to discuss contraception, and they also highlighted a barrier to providing contraceptive counseling as a lack of time [ 6 ]. This qualitative study highlights the possible bias providers experience surrounding patients experiencing pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%